2022
DOI: 10.1021/acs.jced.2c00519
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Surface Tension of Fluorene and Perhydrofluorene Close to 0.1 MPa up to 573 K

Abstract: In the present study, the liquid viscosity and surface tension of fluorene (H0-F) and its fully hydrogenated counterpart perhydrofluorene (H12-F), representing process-relevant byproducts of the liquid organic hydrogen carrier (LOHC) system based on diphenylmethane and dicyclohexylmethane and potentially interesting LOHC compounds by themselves, were determined close to 0.1 MPa using different experimental methods. Besides surface light scattering (SLS) allowing for a simultaneous access to both properties up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The results are presented in Figure , where DSC analysis revealed a prominent absorption peak at a temperature of 390.06 K, indicating the melting process of fluorene. The melting point was determined as the onset temperature of the peak (387.92 K), which was consistent with the reported melting point in the literature . What’s more, the melting enthalpy was measured to be 16.948 kJ/mol.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results are presented in Figure , where DSC analysis revealed a prominent absorption peak at a temperature of 390.06 K, indicating the melting process of fluorene. The melting point was determined as the onset temperature of the peak (387.92 K), which was consistent with the reported melting point in the literature . What’s more, the melting enthalpy was measured to be 16.948 kJ/mol.…”
Section: Resultssupporting
confidence: 81%
“…The melting point was determined as the onset temperature of the peak (387.92 K), which was consistent with the reported melting point in the literature. 19 What's more, the melting enthalpy was measured to be 16.948 kJ/mol. 4.3.…”
Section: Evaluation Of Modelsmentioning
confidence: 99%
“…For the fully hydrogenated systems, the values for η L and σ obtained by SLS and the conventional techniques agree very well, i.e., typically within combined uncertainties. In contrast, the SLS results for η L and σ were often too large and too small for the dehydrogenated systems and, in particular, for systems containing the partially hydrogenated intermediate cyclohexylphenylmethane (H6-DPM) . For the latter systems, it was observed that the largest deviations in σ of up to about −15% appeared at the lowest studied temperatures T close to 303 K and gradually vanished with increasing T up to 573 K. In contrast, the η L values evaluated from SLS agree well with the CV data at the lowest T , but tend to show increasing positive deviations at higher T with maximum deviations of +30%.…”
Section: Introductionmentioning
confidence: 64%